Genetic Components for fruit development and ripening of Coffea canephora pierre ex A. Froehner - de Souza, Carolina Augusto; Rocha, Rodrigo Barros; Alves, Enrique Anastácio; Espindula, Marcelo Curitiba; Ramalho, André Rostand; Teixeira, Alexsandro Lara; Ferrão, Maria Amélia Gava (Coffee Science - ISSN 1984-3909, 2017)
Although normally measured in classes, fruit ripening cycle is a complex trait with expression governed by several genes influenced by the environment, which results in a quantitative trait of the continuous distribution. This study aimed to characterize the genetic components of Coffea canephora fruits ripening cycle in order to quantify the genotypic and environmental effects in the expression of this trait. The number of days and the thermal time for fruit ripening of 130 clones were evaluated over 36 months in design of randomized blocks with six replicates of four plants per plot in OuroPreto do Oeste - RO. The genotypic values and the variance components were estimated using methods of Restricted Maximum Likelihood (REML) and Best Linear not Unbiased Prediction (BLUP) and the dissimilarity among genotypes quantified using hierarchical clustering techniques. Estimates of genetic parameters indicate greater accuracy of thermal time to estimate the fruit ripening cycle, and a predominance of the genotypic effect on the expression of this trait. In the dendrogram it was possible to observe three different fruit ripening groups, which maintained over time. They were also observed genotypes (20%) that changed their classification due to the environmental effect. The observed efficiency of selection associated and the clustering of genotypes with similar ripening cycles subsidize the development of new varieties.